Satire, structure, and postmodernity : reimagining Catch-22 - Dhaliwal, Kieran (2017)
This thesis looks at how Joseph Heller's novel, "Catch-22" can be read using the framework of postmodernity and Mikhail Bakhtin's 'carnival'. It looks at the context of the novel's publication and the various ways it reflects the society of the time as well as how it was generally critiqued when it first came out. The thesis also contrasts the different types of satire in the novel, like Juvenilian and Menippean satire, as well as focuses on its postmodern themes and experimentation. By reading the novel as Menippean satire and with a focus on postmodernism and its aesthetic, the thesis offers a newer or alternative method to read the novel, one based in light of the changing nature satire.